Моно- и бициклические бис-гетероциклы - возможные структурные единицы макрогетероциклов - Бакибаев А. А. Абдигали Абдиманапович; Яговкин А. Ю. Александр Юрьевич; Савченко Т. И. Тамара Иосифовна; Филимонов В. Д. Виктор Дмитриевич (1989, 1989)
В фонде НТБ ТПУ отсутствует